The Gender Perception Towards the Future during the Pandemic - Gabriella Dambrosio; Barbara Sonzogni (Journal of Sociological Research, 2024)
The aim of this paper is to explore the consequences resulting from global emergencies cases, such as the current Covid-19 pandemic, focusing on the perceptions toward the future in a gender perspective. To this end, the analysis investigates results obtained from a web-survey, conducted in 2021, whose target group is characterized by all the Sapienza University of Rome students’ that, during the last three years, have spent an academic mobility period outside Italy or inside Rome. The results obtained show how, generally, women have a more pessimistic view of the present and post pandemic with more clear implications on the emotional relationships and the working life; on the other side, men seem to be more optimistic about the imminent end of the pandemic, believing that Covid-19 period helped them in managing their time and in strengthening the relationship with own family members. This gender perspective is also confirmed by a comparison on the prevailing attitudes and feelings that people declared they experienced during the 2020 pandemic period with respect to the perception of the near future: more in detail, women claim to be more demoralized, depressed and nervous than men that, on the contrary, define themselves proactive and confident.